Organizational Cultural Intelligence: A Competitive Capability for Strategic Alliances in the International Construction Industry. Issue 4 (19th July 2013) - Yitmen, Ibrahim
Abstract Cultural intelligence (CQ) on the organizational level is an organization's capacity to reconfigure its capability to function and manage effectively in culturally diverse environments and to gain and sustain its competitive advantages. This study aims to present a model, examining how organizational CQ through competitiveness framework might potentially affect the strategic alliancing ability of contracting firms operating abroad. The research involves a questionnaire survey conducted with the contracting firms. The research findings support the contracting firms leveraging their cultural intelligence as their main cross‐cultural competence for establishing and increasing the performance of international strategic alliances.